Ketahanan Keluarga Perspektif Maslahah Mursalah dan Hukum Perkawinan di Indonesia - Feni Arifiani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
AbstractFamily resilience is currently a top priority for state initiatives that address a variety of factors that contribute to family resilience, including physical, social, and psychological aspects. Several aspects of the Marriage Law, however, are in the spotlight because they are contentious.